Using the Average Wage Rate to Assess the Merit of Value of Travel Time Savings: A Concern and Clarification - David Hensher (Findings)
There is a renewed reference to relating the value of travel time to the average wage rate with 40 percent mentioned as the benchmark. This rigid link may have had value when interest focussed on a single homogeneous measure of a single trip travel time and working hours were somewhat rigid for the bulk of workers; however with flexible work practices and heterogeneous interpretations of travel time, the imposition of such a strict assumption is both problematic and misleading as suggested in this paper.